Assessment of Tests Constricted by EFL Teachers for Secondary Stage Students and Its Effects on the Students' Achievement - Mohammad Dayij Alqomoul (JETL (Journal of Education, Teaching and Learning), 2023)
The study aimed to estimate the tests constructed by EFL teachers for the secondary stage students in Tafila Directorate of Education and investigating its effect on the students' achievement. The subject of the study consists of all the teachers who teach English language for secondary stage students in Tafila Directorate of Education with a total number of (102 male and female teachers). Six English test papers were chosen intentionally as a sample of the study (3 represents the first secondary class and 3 for the second secondary class). The sample was chosen by the researcher, as it is considered as a cross- representative of all the tests prepared by English language teachers for the secondary stage. The selected sample was applied to two groups of students (20 males and 20 females) from two different schools. Through the results obtained, it was found that the type of the questions has a significant impact on students' achievement. The significance was in favor of the objective questions. Finally, the study touched on some constructive suggestions and recommendations that may interest all who are involved in the educational process.